Consignment stock management for reducing waste items and GHG emissions using remanufacturing, emission penalties and promotional efforts under capacity constraints. Issue 6 (2nd November 2021) - Malleeswaran, B.; Uthayakumar, R.
ABSTRACT: Most business organizations aim is to make as much profit as possible. In this consignment stock model, we discuss the reworking of waste items and reductions of greenhouse gases (GHGs). Here, we determine the GHGs and GHG penalty costs for each manufacturing and remanufacturing lot size. This proposed model is developed to reduce the manufacturer's total cost per unit time without shortages. Also, we introduced a warehouse capacity constraint (CC) for minimizing the holding cost. For the promotional efforts, retailer promotional activity becomes prevalent in the business world, and here the promotional efforts dependent on demand. We exhibit the numerical instance by performing a sensitivity analysis of the model parameters and discussing specific managerial insights using optimization techniques.